Asam Format - Hayat S (Jurnal Kimia dan Kemasan, 1983)
Formic Acid (Methanoic acid), BCOOH is t.ie simplest of the carboxylic.Derives name from "Formica rufa." the red ant. Formicc acid is acolorlcss,fuming liquid with a characteristic pungent odor. It is handled commerciallyin the form 85 and 90% solutions. The principal use of formic acid is in theleather and textil industries although it is also employed as an intermediatein the production of other chemicals.